Conflict escalation in paediatric services: findings from a qualitative study. Issue 8 (4th May 2015) - Forbat, Liz; Teuten, Bea; Barclay, Sarah
Abstract : Objective: To explore clinician and family experiences of conflict in paediatric services, in order to map the trajectory of conflict escalation. Design: Qualitative interview study, employing extreme-case sampling. Interviews were analysed using an iterative thematic approach to identify common themes regarding the experience and escalation of conflict. Participants: Thirty-eight health professionals and eight parents. All participants had direct experience of conflict, including physical assault and court proceedings, at the interface of acute and palliative care. Setting: Two teaching hospitals, one district general hospital and two paediatric hospices in England, in 2011. Results: Conflicts escalate in a predictable manner. Clearly identifiable behaviours by both clinicians and parents are defined as mild, moderate and severe. Mild describes features like the insensitive use of language and a history of unresolved conflict. Moderate involves a deterioration of trust, and a breakdown of communication and relationships. Severe marks disintegration of working relationships, characterised by behavioural changes including aggression, and a shift in focus from the child's best interests to the conflict itself. Though conflicts may remain at one level, those which escalated tended to move sequentially from one level to the next. Conclusions: Understanding how conflicts escalate provides clinicians with a practical, evidence-based framework to identify the warning signs of conflict in paediatrics.